Hi! I need help please. i prefer if this was done using the FOIL method but anything is fine
![Hi I need help please i prefer if this was done using the FOIL method but anything is fine class=](https://us-static.z-dn.net/files/d8f/bdf847bec144ef79c29c413ecb4a8d52.jpg)
[tex] {4x}^{2} + 3x - 10[/tex]
1. Use foil method.
[tex] {4x}^{2} 5x + 8x - 10[/tex]
2. Collect like terms.
[tex] {4x}^{2} + ( - 5x + 8x) - 10[/tex]
3. Simplify.
[tex] {4x}^{2} + 3x - 10[/tex]
Therefor, the answer is.
[tex] {4x}^{2} + 3x - 10[/tex]
Answer:
(x+2)(4x−5)=4x2+3x−10.
Step-by-step explanation:
multiply (x+2)(4x−5)
using FOIL.
((x)+(2))((4x)+((−1)5))=(x)⋅(4x)+(x)⋅((−1)5)+(2)⋅(4x)+(2)⋅((−1)5)=
=(4x2)+(−5x)+(8x)+(−10)=
=4x2+3x−10